1983
DOI: 10.1210/jcem-57-3-603
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Different Assays for the Thyroid-Stimulating Antibody of Graves’ Disease*

Abstract: Various current methods for the assay of the thyroid-stimulating antibody of Graves' disease (TSAb) were assessed for comparative sensitivity and specificity. Five procedures were examined in detail: I) increase in cAMP in human thyroid slices; II) inhibition of [125I]TSH binding to human thyroid membranes, particulate or III) solubilized; IV) inhibition of [125I]TSH binding to guinea pig fat cell membranes, particulate or V) solubilized. The minimum effective concentration of TSH (microunits per ml) in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Recently, TSH receptor related antibodies have become measurable by precise in vitro radioassays (Zakarija et al, 1980;Sugenoya et al, 1979;Loeffler et al, 1983). Most immunoglobulins from untreated Graves' patients competitively inhibit the binding of 125I-TSH to the TSH receptor, and these immunoglobulin activities have been reported to correlate well with thyroid function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, TSH receptor related antibodies have become measurable by precise in vitro radioassays (Zakarija et al, 1980;Sugenoya et al, 1979;Loeffler et al, 1983). Most immunoglobulins from untreated Graves' patients competitively inhibit the binding of 125I-TSH to the TSH receptor, and these immunoglobulin activities have been reported to correlate well with thyroid function.…”
mentioning
confidence: 99%
“…If potent TBII of the blocking type is present in the maternal blood, then it should cause neonatal hypothyroidism by its placental passage as is the case of neonatal Graves' disease (Zakarija et al, 1983).…”
mentioning
confidence: 99%
“…In the present study we used the same labeled bTSH and incubation buffer to determine the TSH receptors on rat fat membranes, so a single class of binding sites was thought to be specific to rat fat membranes. The value of Ka of rat fat membranes was lower than that of high affinity site of human thyroid membranes, although the values of guinea pig fat membranes were reported to be similar to that of human thyroid membranes (Endo et al 1981;Loeffier et al 1983).…”
Section: Discussionmentioning
confidence: 84%
“…Kishihara et al (1981) reported that a single class of binding site for TSH could be observed in guinea pig fat membranes using highly purified labeled bTSH although with relatively crude labeled bTSH two binding sites were detected. On the other hand, Loeffier et al (1983) reported two binding sites for TSH using highly purified TSH. Other reports suggested that ionic strength of incubation buffer affected TSH binding to thyroid membranes (Powell-Jones et al 1980; Pekonen and Weintraub 1980).…”
Section: Discussionmentioning
confidence: 99%
“…High affinity TSH binding activity of Graves' IgG has been shown in guinea pig adipocytes (2)(3)(4), and Tshr cDNA fragments have been obtained by PCR from rat or human retro-orbital tissues, adipose tissue, and fibroblasts (5)(6)(7)(8). In vitro studies indicate that TSH-mediated responses on adipocytes include proliferation, differentiation, survival, and stimulation of specific cellular pathways (9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%